Peningkatan Hasil Belajar IPS Materi Perdagangan Internasional melalui Model Discovery Learning pada Siswa MTs Negeri 4 Gunungkidul - Rugiyana (Jurnal Pendidikan Madrasah, 2022)
This research aims to improve student learning outcomes through the application of the Discovery Learning model. The subject of this study is a student of class XI-B MTs Negeri 4 Gunungkidul for the 2021/2022 school year on IPS subjects in International Trade materials. The study used classroom action research methods conducted through two cycles including planning, implementation, observation, and reflection activities. The results showed an increase in student learning outcomes each cycle. The assessment of student learning outcomes in cycle I obtained an average of 58.5 grades with less criteria and 40.6% completeness, while in cycle II obtained an average score of 71.32 with sufficient criteria and 75% completeness. Discovery learning model can be applied to class XI students in madrasahs to improve learning outcomes.